Comparison of effect of concurrent phone texting on gait speed in young and middle aged healthy subjects - Shah, Vaibhavi R.; Sheth, Megha S. (International Journal Of Community Medicine And Public Health, 2019)
Background: Around the world today, adoption of mobile media phones and its advancement have been growing at dizzying pace in all age groups. People use phone while walking on/crossing roads, climbing stairs, driving cars, etc. Using a smartphone while walking has shown decrease in walking speed and affect dynamic balance by reducing cognitive ability. The objective of study is to see and compare effect of concurrent phone texting while obstacle walking on walking time in young and middle-aged healthy subjects. Methods: An observational study with 100 healthy individuals (50 young and 50 middle-aged) were taken and had to walk on a 15 m walkway with obstacle (approximately 10% of subject’s height) at 8m distance from start without and with texting. The text messages used were all short objective questions and were sent to them approximately 2 steps prior to reaching the obstacle. Their walking time was analyzed. Results: Wilcoxon test used to analyze difference within group. In young people without phone texting it was11.41±1.24 seconds and with texting was14.79±2.67seconds, (z=-6.101, p<0.001) and in middle aged was14.93±1.20 seconds and 20.52±1.87 seconds respectively (z=-6.154, p<0.001). Mann Whitney test used to analyze difference between groups. For without texting in young and middle aged walking time (U=48.0, p<0.001), with texting young and middle aged walking time (U=122.00, p<0.001) and comparing the difference in walking time between young and middle aged with and without phone texting (U=372.5, p<0.001). Conclusions: Phone texting increases walking time in young and middle aged with difference in walking time more in middle aged adults.